Face recognition impairment in small for gestational age and preterm children. (March 2017) - Perez-Roche, T.; Altemir, I.; Giménez, G.; Prieto, E.; González, I.; López Pisón, J.; Pueyo, V.
Highlights: Children born small for gestational age present worse immediate face recognition and delayed face memory compared with children born with an appropriate weight. Face recognition difficulties are detected not only in SGA children born preterm, but also in SGA children born at term. These deficits persist throughout childhood. Prematurity and low birth weight may be an aetiology to explain high rates of developmental prosopagnosia in childhood and adult live. Abstract: Background: Infants born prematurely or with low birth weight are at increased risk of visual perceptual impairment. Face recognition is a high-order visual ability important for social development, which has been rarely assessed in premature or low birth weight children. Aims: To evaluate the influence of prematurity and low birth weight on face recognition skills. Methods: Seventy-seven children were evaluated as part of a prospective cohort study. They were divided into premature and term birth cohorts. Children with a birth weight below the 10th centile were considered small for gestational age. All children underwent a full ophthalmologic assessment and evaluation of face recognition skills using the Facial Memory subtest from the Test of Memory and Learning. Results: Premature infants scored worse on immediate face recognition compared to term infants. However, after adjusting for birth weight, prematurity was not associated with worse outcomes. Independent of gestational age, outcomes of low birth weight children were worse than those of appropriate birth weight children, for immediate face recognition (odds ratio [OR], 5.14; 95% confidence interval [CI], 1.32–21.74) and for face memory (OR, 4.48; 95% CI, 1.14–16.95). Conclusions: Being born small for gestational age is associated with suboptimal face recognition skills, even in children without major neurodevelopmental problems.